Alterations in plasma kynurenine pathway metabolites in children and adolescents with bipolar disorder and unaffected offspring of bipolar parents: A preliminary study. (7th November 2020) - Benevenuto, Deborah; Saxena, Kirti; Fries, Gabriel R.; Valvassori, Samira S.; Kahlon, Ramandeep; Saxena, Johanna; Kurian, Sherin; Zeni, Cristian P.; Kazimi, Iram F.; Scaini, Giselli; Soares, Jair C.; Quevedo, João
Abstract: Background: There has been growing scientific evidence in recent years that bipolar disorder (BD) is associated with alterations in the kynurenine (KYN) pathway. However, many of these studies have been limited by their focus on adults. Thus, this preliminary study investigated differences in the peripheral levels of KYN metabolites in children and adolescents with BD, unaffected offspring of parents with BD, and healthy controls (HCs). Methods: Plasma samples were collected from 49 youths with BD, 19 bipolar offspring, and 31 HCs. Tryptophan (TRP), KYN, and kynurenic acid (KYNA) were separated using electrospray ionization. Results: One‐Way ANCOVA after controlling for age, gender, race, BMI‐for‐age, and smoking status showed that BD had lower levels of KYN, while unaffected high‐risk offspring subjects had lower levels of TRP, KYN, and KYNA when compared to HCs. Moreover, we found that KYN, KYN/TRP, and KYNA/KYN levels predicted the severity of depressive symptoms, while the YMRS score was not associated with any metabolite. Conclusions: In summary, this preliminary study has shown that KYN metabolites are decreased in both affected and unaffected subjects, strengthening the idea that the KYN pathway might underlie the familial risk of BD shown by high‐risk offspring individuals. However, longitudinal studies are needed to examine whether the alterations observed in this study represent early markers of risk for later developing BD.